Case Report of Urethritis in a Male Patient Infected with Two Different Isolates of Multiple Drug-Resistant Neisseria gonorrhoeae - Al-Madboly, Lamiaa; Gheida, Shereen (Frontiers in Medicine, 2017)
We report a brief description of a case suffering from bacterial urethritis, conjunctivitis and arthritis, caused by two different isolates of multiple drug resistant Neisseria gonorrhoeae. Initial diagnosis was dependent on the patient history, clinical findings, symptoms, and the bacteriological data. Polymerase chain reaction confirmed the identification of the pathogens. Random Amplified Polymorphic DNA revealed two different patterns. Susceptibility testing was performed using Kirby-Bauer disk diffusion method and the minimum inhibitory concentration was also determined. It revealed multiple drug resistance associated with β-lactamase production. Only gentamicin, rifampicin and azithromycin were active against the test pathogens. A dual therapy was initiated using gentamicin as well as azithromycin to treat the possible co-infection with Chlamydia trachomatis. Complete recovery of the patient achieved with resolved symptoms a week later.